Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Berbantuan LKPD Terhadap Kemampuan Berpikir Kreatif Fisika Peserta Didik di SMAN 3 Mataram - Yuli Yuli; Hairunnisyah Sahidu; Syahrial Ayub (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
Abstract Ã¢â¬â This study aimed to find out the effect of cooperative learning model Numbered Heads Together (NHT) LKPD aided in the ability to think creatively physics learners in SMAN 3 Mataram. Type of research used quasi-experiment with non-equivalent research design or untreated control group design with pre-test and post-tes. The population of all students of class XI MIA SMAN 3 Mataram, amounting to 349 people. Sampling research using purposive sampling technique, so selected XI class MIA 3 as experimental class and XI MIA 4 as a control class. The experimental class was given treatment in the form of cooperative learning model of NHT type supported by LKPD and control class was given treatment in the form of direct teaching model. The data collection of creative thinking ability is done by the form of a description test as many as 10 questions consisting of 7 questions of verbal creativity and 3 figural creativity questions. Creativity data was analyzed by using t-test polled variance at 5% significant level with degrees of freedom 73. The results of research on the influence of cooperative learning model type NHT assisted LKPD on the ability of creative thinking physics learners obtained tcontinue > t(0,05;73) = 3,63 > 2,00. Based on the results of this analysis can be concluded that cooperative learning model type NHT aided LKPD effect on the ability of creative thinking physics learners in SMAN 3 Mataram.